IMPLEMENTATION OF INFORMATION RESILIENCE OF INDONESIA-MALAYSIA BORDER REGION IN RIAU PROVINCE - Irdayanti, Irdayanti; Salmiyati, Salmiyati; Nurlita, Anna (Universitas Negeri Yogyakarta, 2022)
Indonesia's border area is located along the Indonesian border with other countries. In general, border areas are still lagging behind other regions in Indonesia. Besides the minimal basic needs, other needs have not been appropriately met, namely the need for information in the country and the penetration of television broadcasts from Malaysia. This study aims to describe how the implementation of information security in border areas, especially in Riau province, through the operational concept of David L. Weimer and Aidan R. Vining. This research uses a qualitative approach through a case study, namely Rupat Island. The data collection method in this study was through observations in border areas and interviews with government employees of Bengkalis Regency and border communities, which were carried out from January 2021 to November 2021. The results showed that information security in border areas led to improved telecommunications infrastructure, which proliferated. Apart from that, local governments continue to build access to public information. However, border communities are still lagging in television and radio broadcasting. In addition to the ease of accessing Malaysian television channels, in general, the socio-cultural life of people in border areas is constructed from the Malaysian television channel programs they enjoy.